Threats to identity: lipodystrophy and identity changes in people with HIV/AIDS (PWA) - Mancini, Tiziana; Secchiaroli, Gianfranco (Acta Biomedica Atenei Parmensis, 2015)
Background and aim: PWA today have to face new problems associated with their disease state. One of these is tied to bodily changes that are related to HAART (lipodystrophy syndrome, LDS). Applying the Identity Process Theory (Breakwell, 1986), this research aimed to study the impact that LDS body changes may have on the identity of PWA. Method: One hundred and eight patients (79 M and 29 F, ranging from 35 to 75 years old) at a North Italian clinic completed a questionnaire composed of scales measuring the perception of threats to the identity of PWA, physicians’ and patients’ assessment of LDS, time from diagnosis, disclosure and perceived social support. Results: Results showed that lipodystrophy changes represent a new aspect of the disease that PWA need to handle in terms of identity: the changes resulted in ‘loss of the self’ and constituted a particular threat to the dimension of personal identity whereby bodily changes called more into question the principles of self-esteem and distinctness. LDS, however, lead to a multiple identity threat that is aggravated by patients’ perception of the severity of their bodily changes and by the perception of a lack of friendship and social support. Conclusions: The study highlights how complex, cyclical and dynamic are the effects that HIV status can have on the sick person: they are no longer only clinical, but also psychological and psychosocial.